PRIORITY ISSUES OF THE DEVELOPMENT OF LEGAL EDUCATION IN THE REPUBLIC OF UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes legal education, its specific features, the concept of legal education, and the expected results of legal education.